Ritual Mutilation of Europeans on the Torres Strait Maritime Frontier. Issue 3 (3rd July 2018) - McNiven, Ian J.
ABSTRACT: Passage through the Torres Strait during the late 18th and early 19th centuries was a dangerous exercise for European mariners. Apart from a maze of largely unmapped reefs, mariners had to negotiate passage through waters inhabited by resident Indigenous communities who had acquired a reputation for brutal attacks and cruel treatment of castaways. This paper explores circumstances behind the murder and mutilation of crew and passengers by Torres Strait Islanders from five ships attempting to transit the Strait – Shaw Hormuzear / Chesterfield (1793), Charles Eaton (1834), Thomas Lord (1846), and Sperwer (1869). Using anthropological recordings from the late 19th century, these mutilations are recast as acts of ritual processing explicable with reference to Torres Strait Islander ontology. The circumstances that coalesced to precipitate these mutilations were complex and rare and ultimately unrepresentative of the majority of frontier interactions between European mariners and Torres Strait Islanders, which were generally friendly and mutually beneficial.